Versatile Precoder Codebook Design Method for Orthogonal Space-Time Block Codes - Kang, E.; Sayeed, A.M. (2006 IEEE International Symposium on Information Theory, 2006)
Many techniques have been proposed to improve the error performance of multiple antenna systems by having the receiver provide the transmitter with channel information, which guides the transmitter to adapt its transmission. However, existing works have focused on ideal situations of i.i.d. communication channels and instantaneous feedback channels, or have not used the limited number of feedback bits efficiently. This paper proposes a versatile precoder codebook design method that works well for general situations, i.e. spatially correlated communication channels and feedback channels with delay, using feedback bits efficiently. This method finds a good codebook by directly quantizing a codebook (not a channel realization) with error probability as a performance measure. Numerical studies demonstrate that (1) the codebook generated this way achieves bit error rates as good as or better than what other codebooks yield because our codebook has been optimized for error probability without imposing any limiting structure, and (2) our codebook with fewer feedback bits outperforms the channel quantization-based codebook with more feedback bits due to the efficient use of the feedback bits